Red Grange: The Life and Legacy of the NFL's First Superstar - Willis, Chris (Rowman & Littlefield Publishers, 2019)
In celebration of the National Football League’s 100th season, noted football historian Chris Willis brings to life the story of Red Grange, the nation’s first NFL star, in this definitive biography. Harold “Red” Grange became a national sensation as a junior halfback at the University of Illinois in the 1920s. He quickly joined other great athletes of the Roaring Twenties such as Bobby Jones, Jack Dempsey, and Babe Ruth in enthralling audiences on the radio and in newspapers on a daily basis. A year later the "Galloping Ghost" stunned the country by dropping out of school after his last collegiate game and going pro with the six year old NFL, signing with the Chicago Bears. In Red Grange: The Life and Legacy of the NFL’s First Superstar, Chris Willis tells the remarkable story of a humble football player who rose to fame in the 1920s and became an icon. With unlimited access and complete cooperation of the Grange family, Willis offers new insight into Grange’s rags-to-riches story, including details about his tomboy mother who died when Grange was six years old and never-before-published information on Grange’s barnstorming tour with the Chicago Bears that instantly gave credibility to the fledgling NFL. With over fifty original interviews, personal letters to and from Grange, and more than forty photos, this definitive biography reveals in intimate detail the life of a sports pioneer. Whether as a player, coach, broadcaster, pitchman, Hall of Famer, ambassador, or icon, Red Grange was, and still is, the face of the early NFL and one of the greatest athletes of all-time.